Behavioral Consequences of a Combination of Gad1 Haplodeficiency and Adolescent Exposure to an NMDA Receptor Antagonist in Long-Evans Rats - Fujihara, Kazuyuki; Sato, Takumi; Higeta, Kazuya; Miyasaka, Yoshiki; Mashimo, Tomoji; Yanagawa, Yuchio (Frontiers in Pharmacology, 2021)
Glutamate decarboxylase 67-kDa isoform (GAD67), which is encoded by the GAD1 gene, is one of the key enzymes that produce GABA. The reduced expression of GAD67 has been linked to the pathophysiology of schizophrenia. Additionally, the excitatory glutamatergic system plays an important role in the development of this disorder. Animal model studies have revealed that chronic blockade of NMDA-type glutamate receptors can cause GABAergic dysfunction and long-lasting behavioral abnormalities. Based on these findings, we speculated that Gad1 haplodeficiency combined with chronic NMDA receptor blockade would lead to larger behavioral consequences relevant to schizophrenia in a rat model. In this study, we administered an NMDAR antagonist, MK-801 (0.2 mg/kg), to CRISPR/Cas9-generated Gad1+/– rats during adolescence to test this hypothesis. The MK-801 treated Gad1+/– rats showed a shorter duration in each rearing episode in the open field test than the saline-treated Gad1+/+ rats. In contrast, immobility in the forced swim test was increased and fear extinction was impaired in Gad1+/– rats irrespective of MK-801 treatment. Interestingly, the time spent in the center region of the elevated plus-maze was significantly affected only in the saline-treated Gad1+/– rats. Additionally, the MK-801-induced impairment of the social novelty preference was not observed in Gad1+/– rats. These results suggest that the synergistic and additive effects of Gad1 haplodeficiency and NMDA receptor blockade during adolescence on the pathogenesis of schizophrenia may be more limited than expected. Findings from this study also imply that these two factors mainly affect negative or affective symptoms, rather than positive symptoms.